2003
DOI: 10.1046/j.1365-2265.2003.01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in acromegaly: the effect of gender, disease activity and gonadal status

Abstract: The anabolic effect of GH excess on bone in acromegalic patients is: (i) gender-independent; (ii) evident at the spine only in eugonadal regardless of disease activity; (iii) evident at femoral neck only in the presence of active disease regardless of gonadal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 17 publications
0
45
2
1
Order By: Relevance
“…However, a recent study demonstrated a high prevalence of vertebral fractures in postmenopausal women with acromegaly in relation to disease activity (21). Thus, gonadal status has been proposed to be an important determinant of excess GH (7,13,15,17), and it is possible that trabecular bone, with its more intimate contact with the circulation, is influenced by sex steroids to a greater extent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study demonstrated a high prevalence of vertebral fractures in postmenopausal women with acromegaly in relation to disease activity (21). Thus, gonadal status has been proposed to be an important determinant of excess GH (7,13,15,17), and it is possible that trabecular bone, with its more intimate contact with the circulation, is influenced by sex steroids to a greater extent.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, acromegaly was traditionally associated with osteoporosis (12)(13)(14). Later studies have revealed a differential effect of GH excess on the axial (70% trabecular bone) and appendicular skeleton (90% cortical bone) with unchanged or reduced vertebral bone density and increased forearm bone density (1,3,(13)(14)(15)(16)(17), while some studies show no differences in acromegalic patients compared with normal controls (4,18,19). However, measurement of bone mineral density (BMD) in the axial skeleton, as an indicator of trabecular bone mass, may be overestimated in endocrine disorders affecting bone size and the distribution between trabecular and cortical envelopes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In active acromegaly, high circulating concentrations of GH and IGF1 are associated with increased cortical BMD (6)(7)(8)(9)(10). The reported effects of GH/IGF1 excess on trabecular BMD are more variable, with studies reporting either increased or decreased BMD at trabecular sites possibly due to the variable presence of hypogonadism (1,(3)(4)(5)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that the anabolic effects of GH on bone mineral density (BMD) may be sustained after cure of acromegaly (1)(2)(3)(4)(5), but duration of follow-up was relatively short in the majority of studies. The effects of GH excess on BMD appear to be less consistent.…”
Section: Introductionmentioning
confidence: 99%